Professor Dr. Badhrulhisham, the new Deputy VC - UMP, PNC
Professor Dr. Badhrulhisham Abdul Aziz, has been appointed Universiti Malaysia Pahang (UMP)’s Deputy Vice-Chancellor (Academic & International) for three years, effective from June 1, 2010 until May 31, 2013. He replaces Professor Dato’ Dr. Sabarudin Mohd.